2006
DOI: 10.1016/j.ymthe.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Fully Deleted Adenovirus Persistently Expressing GAA Accomplishes Long-Term Skeletal Muscle Glycogen Correction in Tolerant and Nontolerant GSD-II Mice

Abstract: Glycogen storage disease type II (GSD-II) patients manifest symptoms of muscular dystrophy secondary to abnormal glycogen storage in cardiac and skeletal muscles. For GSD-II, we hypothesized that a fully deleted adenovirus (FDAd) vector expressing hGAA via nonviral regulatory elements (PEPCK promoter/ApoE enhancer) would facilitate long-term efficacy and decrease propensity to generate anti-hGAA antibody responses against hepatically secreted hGAA. Intravenous delivery of FDAdhGAA into GAA-tolerant or nontoler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…For example, intravenous injection of HDAd expressing the canine coagulation factor IX in hemophilia B dogs resulted in sustained phenotypic improvement of the bleeding diathesis for the duration of the experiment of over 1 year after vector administration. 3 These, as well as other recent studies, [4][5][6][7][8][9][10][11][12][13] provide compelling evidence for using HDAd to treat genetic disorders.…”
Section: Prospectsmentioning
confidence: 81%
“…For example, intravenous injection of HDAd expressing the canine coagulation factor IX in hemophilia B dogs resulted in sustained phenotypic improvement of the bleeding diathesis for the duration of the experiment of over 1 year after vector administration. 3 These, as well as other recent studies, [4][5][6][7][8][9][10][11][12][13] provide compelling evidence for using HDAd to treat genetic disorders.…”
Section: Prospectsmentioning
confidence: 81%
“…8,11,12 Furthermore, we have recently shown that several rapid immune responses, typically noted after systemic Ad vector injections into Ad-naive mice, are also significantly impacted upon by the presence of a fully functional complement system. 12,18 For example, multiple cytokines and chemokines, noted to rise to significant levels in the plasma of Ad-injected wild-type (WT) mice, do so in a C3-dependent manner in vivo. 12 More dramatically, we have shown that the utilization of rAds both in vitro and in vivo results in a rapid and profound change in the cellular transcriptome, with a high percentage of these genes being rapidly induced (or repressed) by Ads in a C3-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose tetrasacchride has been used as a biomarker for monitoring the therapeutic response to ERT in Pompe's disease [17]. The enzyme is present in fibroblasts grown from amniotic fluid cells and can be utilized for prenatal diagnosis as well [18,19]. Gene encoding of acid alpha-glucosidase has been localized to band 17q23 and gene therapy is in the early stages of preclinical investigation.…”
Section: Discussionmentioning
confidence: 99%